من أدب الحكمة الرافدية (Damascus University Journal of arts and humanities sciences, 2022)
This research aims to shed light on one of the most important ancient Mesopotamian literary chapters, which is “The Literature of Wisdom.” The Mesopotamian Code is hardly devoid of wise references that are highly relevant to values, morals and ideals in life. The ancient Mesopotamians wrote them down in their daily lives through  Their long history.  Where the Mesopotamian wisdom received a high position and an eloquent interest in Mesopotamian literature in general, and this study is only to focus on the process of Mesopotamian wisdom literature and its manifestations from the late fourth millennium BC to the seventh century BC.